A Bio‐Psychosocial Intervention Program for Improving Quality of Life in Breast Cancer Survivors – Final Outcome of a Prospective Randomized Trial. Issue 5 (24th February 2017) - Pettiford, Janine; Felts, Sharon; Wischkaemper, Edna; Miller, Debbie; Crawford, Sybil; Layeequr Rahman, Rakhshanda
Abstract: Given the 3.1 million breast cancer survivors in America, quality of life (QoL) is a vital issue. Bio‐psychosocial milieu of survivorship is increasingly important. This study assesses the impact of Bio‐psychosocial Intervention (BPSI) on the QoL of breast cancer survivors utilizing Functional Assessment of Cancer Therapy – Breast (FACT‐B) instrument. A prospective randomized trial was designed; intervention arm included a 4‐hour BPSI coping skills class; control arm received standard of cancer and follow‐up care (SOC). Women diagnosed within 2 years of study initiation were eligible. Sample size was based on 8‐point difference in FACT‐B score, 90% power, 5% type I error, and 20% attrition. FACT‐B questionnaire was administered to all patients at baseline and at 6‐month intervals. SAS 9.3 software was used to analyze data using Chi‐square test for categorical and Wilcoxon rank sum for ordinal data; linear mixed modeling was used for longitudinal analysis. One‐hundred and three of 120 (86%) patients were available for analysis. Forty‐seven patients were in BSPI arm, and 56 received SOC. For BPSI arm versus SOC arm, the median (interquartile) age (60 [52.68] versus 58 [52.68] years, p = 0.9135), cancer‐stage (0:1:2:3 = 11%:41%:35%:13% versus 18%:46%:22%:15%, p = 0.4645), and biology (ER+:triple negative:HER2+ = 74%:9%:16% versus 72%:7%:20%, p = 0.8454), respectively, was similar. Median (25th to 75th centile) FACT‐B scores in BPSI versus SOC arms at baseline were 109 (95.121) versus 112 (95, 122) (p = 0.6125); mean (SE) change since baseline at 6, 12, 18, and 24 months was: 7.42 (2.22) versus 7.04 (1.97) (p = 0.8862); 17.0 (2.64) versus −6.09 (2.37) (p < 0.0001); 16.03 (2.53) versus 3.58 (2.29) (p = 0.0004), and 15.48 (1.89) versus 16.4 (1.71) (p = 0.7966), respectively. The inter‐group differences remained after adjusting for confounding variables at baseline. The p‐value for interaction among groups over 2 years remained <0.0001 except for breast cancer specific concerns. BPSI coping skills class significantly improved the QoL of breast cancer survivors by 1 year post‐intervention time point; this difference narrowed at 18 months and disappeared at 24 months.